1985
DOI: 10.1115/1.3267660
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Steam Gasification of Biomass for Methanol and Methane Production

Abstract: The technical and economic feasibility of producing specific gas products by the catalytic gasification of biomass is presented in this paper. Active catalysts were developed for generation of synthesis gases from wood by steam gasification. A trimetallic catalyst, Ni-Co-Mo on silica-alumina doped with 2 wt% Na, was found to retain activity indefinitely for generation of a methanol synthesis gas from wood at 750° C (1380° F) and 100 kPa (1 atm) absolute pressure. Potassium carbonate was an effective catalyst f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 0 publications
2
37
0
Order By: Relevance
“…[336][337][338][339][340] These alkanes have high cetane numbers (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65), and a 10-month on-road test of six postal delivery vans showed that engine fuel economy was greatly improved by a blend of petrodiesel with hydrotreated vegetable oil products. 340 The reaction conditions for the hydrotreating process are 350-450°C, 40-150 atm, liquid hourly space velocities 0.5-5.0 h -1 , and sulfided NiMo/Al 2 O 3 catalysts.…”
Section: Hydrotreatingmentioning
confidence: 99%
“…[336][337][338][339][340] These alkanes have high cetane numbers (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65), and a 10-month on-road test of six postal delivery vans showed that engine fuel economy was greatly improved by a blend of petrodiesel with hydrotreated vegetable oil products. 340 The reaction conditions for the hydrotreating process are 350-450°C, 40-150 atm, liquid hourly space velocities 0.5-5.0 h -1 , and sulfided NiMo/Al 2 O 3 catalysts.…”
Section: Hydrotreatingmentioning
confidence: 99%
“…One catalyst was tested for over lo00 h and was still active when the test was terminated +Operated for the U.S. Department 0888-5885187 f 2626-I335$0I.50/0 0 Mudge, et al, 1985). One catalyst was tested for over lo00 h and was still active when the test was terminated +Operated for the U.S. Department 0888-5885187 f 2626-I335$0I.50/0 0 Mudge, et al, 1985).…”
mentioning
confidence: 99%
“…In addition, oxygen has a function to delay the catalyst deactivation by helping burn off some of the coke formed. Earlier, for example, Mudge et al investigated the catalytic steam gasification of wood using alkali carbonates and naturally occurring minerals (trona, borax), which were either impregnated or mixed with the biomass (Mudge and Baker, 1985). Nevertheless, tar can be effectively minimized by catalytic cracking.…”
Section: Gasification Of Biomass Gasificationmentioning
confidence: 99%